The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41598-023-49674-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review reveals that African children of 15–17 years demonstrate low hepatitis B vaccine seroprotection rates

Fahad Muwanda,
Hakim Sendagire,
Gerald Mboowa
et al.

Abstract: Childhood HBV immunization remains globally fundamental to the elimination of hepatitis B virus (HBV). However, monitoring proportions of HBV vaccine seroprotection and their determinants among African Pediatric recipients is crucial. This study sought to verify extent of immune protection accorded by the HBV vaccine in African children of up to 17 years of age by pooling the prevalence of seroprotection reported by primary studies conducted in the Northern, Western, and Southern African regions. We included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Similar findings were observed in the study done in Iran which showed high vaccine coverage among children [23] . The observation of the majority of children especially those below 15 years being fully vaccinated is further supported by a recent systematic review from Africa that found a significantly higher proportion of HBV vaccine seroprotection among children under 15 years of age than children 15-17 years, linking this to successful implementation of the HBV vaccine on the extended programs on immunizations in Africa [11] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar findings were observed in the study done in Iran which showed high vaccine coverage among children [23] . The observation of the majority of children especially those below 15 years being fully vaccinated is further supported by a recent systematic review from Africa that found a significantly higher proportion of HBV vaccine seroprotection among children under 15 years of age than children 15-17 years, linking this to successful implementation of the HBV vaccine on the extended programs on immunizations in Africa [11] .…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, even in low prevalence areas, certain populations such as drug abusers, men who have sex with men, and people living with HIV have high proportions of chronic HBV infection [10] . In addition, a recent systematic review has revealed that children between 15 and 17 years in Africa have lower hepatitis B vaccine seroprotection rate than children below 15 years [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that adolescents aged 10 years and above were at significantly higher risk of lost seroprotection. Markedly low hepatitis B vaccine seroprotection among adolescents who completed their vaccinations during infancy was also witnessed in various other African countries according to a recently published systemic review [21]. Peak anti-HBs concentration achieved after primary vaccination and age-dependent decay in anti-HBs titers play key roles in protection against infection [16].…”
Section: Discussionmentioning
confidence: 97%